Recurrence following hemithyroidectomy in patients with low‐ and intermediate‐risk papillary thyroid carcinoma. Issue 6 (5th February 2020) - Ahn, D.; Lee, G. J.; Sohn, J. H.
Abstract : Background: This study evaluated the incidence, patterns and risk factors for recurrence after hemithyroidectomy in patients with low‐ and intermediate‐risk papillary thyroid carcinoma (PTC), and verified the predictive role of the risk staging systems in current use. Methods: The clinicopathological characteristics and risk categories were analysed according to recurrence in patients who underwent hemithyroidectomy for low‐ and intermediate‐risk conventional PTC, and were followed up for at least 24 months. Five risk staging systems were used to stratify risk: the 2015 American Thyroid Association (ATA) system; Age, Metastases, Extent and Size (AMES) system; Metastases, Age, Complete resection, Invasion and Size (MACIS) system; Grade, Age, Metastases, Extent and Size (GAMES) system; and the eighth AJCC system. Results: The study included 561 patients; 93·9 per cent of the study population (527 of 561) had a papillary thyroid microcarcinoma 1 cm or smaller in size. At a mean follow‐up of 83 months, 25 patients (4·5 per cent) had recurrence; among these patients, 23 (92%) presented with a remaining thyroid lobe. Multifocality was significantly associated with recurrence in univariable and multivariable analyses (adjusted hazard ratio 3·16, 95 per cent c.i. 1·25 to 7·98; P  = 0·015). Disease‐free survival (DFS) varied according to multifocality ( P  = 0·010). The five risk staging systems were not associated with recurrence, and their Harrell's C‐index ranged from 0·500 to 0·531. DFS rates did not differ between the risk categories in each system. Conclusion: Although the recurrence rate after hemithyroidectomy in patients with low‐ and intermediate‐risk PTC was low, meticulous follow‐up focusing on the remaining thyroid lobe is needed for early detection and timely management of recurrence. The risk scoring systems in current use have no predictive role in these patients. Abstract : In this study, the overall recurrence rate after hemithyroidectomy in patients with low‐ to intermediate‐risk papillary thyroid carcinoma was 4·5 per cent (25 of 561), and most recurrences developed in the retained contralateral thyroid lobe. Multifocality was significantly associated with recurrence. However, none of the currently used risk staging systems (2015 American Thyroid Association (ATA); Age, Metastases, Extent and Size (AMES); Metastases, Age, Complete resection, Invasion and Size (MACIS); Grade, Age, Metastases, Extent and Size (GAMES); and 8th AJCC) were associated with recurrence. Recurrence rate low Abstract : Antecedentes: Este estudio evaluó la incidencia, patrones y factores de riesgo de recidiva tras hemitiroidectomía en pacientes con carcinoma papilar de tiroides ( papillary thyroid carcinoma, PTC) de riesgo bajo e intermedio y verificó el papel predictivo de los sistemas de estadificación del riesgo utilizados en la actualidad ( risk staging systems, RSSs). Métodos: Se analizaron las características clinicopatológicas y las categorías de riesgo en base a la recidiva en 561 pacientes que fueron sometidos a hemitiroidectomía por PTC convencional de riesgo bajo e intermedio y seguidos durante ≥ 24 meses. Para estratificar el riesgo se utilizaron cinco RSSs, incluyendo el sistema de la American Thyroid Association (ATA) de 2015; la edad, las metástasis, la extensión y el tamaño del sistema AMES; las metástasis, la edad, la resección completa, la invasión y el tamaño del sistema GAMES; y la octava edición de la American Joint Committee on Cancer system (AJCC). Resultados: La proporción de la población de estudio con microcarcinoma papilar de tiroides de tamaño ≤ 1 cm fue 93, 9% (527/561). A los 83 meses de seguimiento, 25 pacientes (4, 5%) presentaron recidiva y entre estos pacientes, 23 (92%) no habían sido sometidos a tiroidectomía total. La multifocalidad se asoció significativamente con la recidiva en los análisis univariado y multivariable con un cociente de riesgos instantáneos ( hazard ratio, HR) ajustado de 3, 163; i.c. del 95% 1, 253–7, 983; P = 0, 015. La supervivencia libre de enfermedad ( disease‐free survival, DFS) varió según la multifocalidad ( P = 0, 010). Los cinco RSSs no se asociaron con la recidiva, y su índice C de Harrell fue 0, 500‐0, 531. Las DFSs no fueron diferentes entre las categorías de riesgo de cada RSS. Conclusión: La tasa de recidiva tras hemitiroidectomía en pacientes con PTC de riesgo bajo e intermedio fue baja. Sin embargo, es necesario efectuar un seguimiento meticuloso, centrándose en el lóbulo tiroideo restante, para la detección precoz y el tratamiento oportuno de la recidiva. Los RSSs que se utilizan en la actualidad no tienen valor predictivo en estos pacientes.